Anemia, hematinic deficiencies, hyperhomocysteinemia, and gastric parietal cell antibody positivity in burning mouth syndrome patients with vitamin B12 deficiency - Chiang, Meng-Ling (J Dent Sci, 2020)
BACKGROUND/PURPOSE: Our previous study found that 42 of 884 burning mouth syndrome (BMS) patients have vitamin B12 deficiency. This study assessed whether the vitamin B12-deficient BMS (B12D/BMS) patients had significantly higher frequencies of anemia, hematinic deficiencies, hyperhomocysteinemia, and serum gastric parietal cell antibody (GPCA) positivity than healthy control subjects and evaluated whether all B12D/BMS patients had pernicious anemia (PA). MATERIALS AND METHODS: The blood hemoglobin (Hb) and serum iron, vitamin B12, folic acid, homocysteine, and GPCA levels in 42 B12D/BMS patients and 442 healthy control subjects were measured and compared. RESULTS: We found that 42 B12D/BMS patients had significantly lower mean blood Hb and serum iron and vitamin B12 levels as well as significantly higher mean corpuscular volume (MCV) and mean serum homocysteine level than healthy control subjects (all P-values < 0.05). Moreover, 42 B12D/BMS patients had significantly higher frequencies of macrocytosis (52.4%), blood Hb (61.9%) and serum iron (26.2%) and vitamin B12 (100.0%) deficiencies, hyperhomocysteinemia (83.3%), and serum GPCA positivity (42.9%) than 442 healthy control subjects (all P-values < 0.001). Moreover, of 26 anemic B12D/BMS patients, 15 (57.7%) had PA, 5 (19.2%) had macrocytic anemia other than PA, 4 (15.4%) had normocytic anemia, and 2 (7.7%) had thalassemia trait-induced anemia. CONCLUSION: B12D/BMS patients have significantly higher frequencies of macrocytosis, blood Hb and serum iron and vitamin B12 deficiencies, hyperhomocysteinemia, and serum GPCA positivity than healthy control subjects. Although PA is the most common type of anemia in our B12D/BMS patients, only 15 (35.7%) of 42 B12D/BMS patients have PA.